NANOFORMS: A NEW TYPE OF PROTEIN-ASSOCIATED MINERALIZATION - Vali H.; McKee M.D.; Ciftcioglu N.; Sears S.K.; Plows F.L.; Chevet E.; Ghiabi P.; Plavsic M.; Kajander E.O.; Zare R.N. (My University, 2001)
Controversy surrounds the interpretation of various nano-phenomena as being living organisms. Incubation of fetal bovine serum under standard cell culture conditions results in the formation of free entities in solution, here referred to as nanoforms. These nanoforms, when examined by transmission electron microscopy, have a distinct ovoid morphology ranging in size from tens to hundreds of nanometers. They are composed of hydroxyapatite and proteins and constitute a novel form of protein-associated mineralization. No detectable cell structure resembling bacteria is apparent. However, immunodetection of the proteins associated with the nanoforms, by two specific monoclonal antibodies, suggests a possible biogenic origin. The significance of nanoforms for the recognition of biological activity in ancient geological systems is discussed. The mode of mineralization in nanoforms is also compared to matrix-mediated calcification in vertebrates.